LMO2 plays differential roles in trophoblast subtypes and is associated with preeclampsia - Chen, Yaxin; Meng, Yingying; Yu, Yanhong; Li, Wen; Shen, Yongmei; Li, Shanshan; Chang, Ying; Sun, Wei (Biochemical and biophysical research communications, 2022)
Preeclampsia (PE) is a common obstetric disease caused by placenta development abnormality, typically characterized as inadequate trophoblast invasion and spiral artery remodeling. In this study, we found that LMO2 level was decreased in both cytotrophoblast (CTB) and interstitial extravillous trophoblast (iEVT) in human PE placentas, and LMO2 selectively promoted cell migration in iEVT derived HTR-8/SVneo cells whereas increased proliferation in CTB derived JEG-3 cells. In mechanism, LMO2 interacted with NCKAP1, leading to destruction of WAVE regulatory complex and increased lamellipodia formation in HTR-8/SVneo cells, whereas interacted with β-catenin and up-regulated a number of core Wnt/Hippo pathway target genes in JEG-3 cells. This study revealed the differentially functional patterns of LMO2 in different trophoblast subtypes, and suggested LMO2 as a novel target for PE prediction, prevention and treatment in clinical. [Display omitted] •Compared with normal placenta, LMO2 showed decreased expression level in both CTBs and EVTs in preeclampsia placentas.•LMO2 increased cell migration in iEVT derived HTR-8/SVneo cells via targeting to NCKAP1.•LMO2 promoted cell proliferation in CTB derived JEG-3 cells via targeting to beta-Catenin.